ANALISIS KINERJA TRANSMISI SISTEM PEMBANGKIT LISTRIK TENAGA MINI HIDRO (PLTM) DESA TALUDA’A KABUPATEN BONE BOLANGO - Abdul Rahim; Burhan Liputo; Romi Djafar; Yunita Djamalu (Program Vokasi-Universitas Negeri Gorontalo, 2023)
The Mini Hydro Power Plant (PLTM) is an electricity facility located in Ilohuuwa Village, Bone District, Bone Bolango Regency, Gorontalo Province, using the irrigation channels of the Taludaa River and the Iya River. In the working area of ​​PT. PLN (Persero) Sultenggo Region, Gorontalo Branch. PLTM Taludaa Unit I always plans its operating system to obtain maximum electricity production according to targets every year. However, every generator will generally experience many problems with airflow and components that hinder the process of using electrical energy so that it can grow. The analysis results show that the transmission used is a shaft that is 3M long, and the post weighs 83 kg. The shaft is the transmission link from the turbine to the generator. Then, with the flywheel, it is just balancing the rotation or (Balancing) with a flywheel weight of 76 kg and the moment of inertia that is considered. It is 121.60kg/m2. Then, with the bearing resistance, the bearing life has been calculated based on the load and rotation speed. The greater the load and rotation speed, the smaller the bearing life. The results obtained are 14.5457 working hours, 6060 per day, 119 per month, and 16.6 per year, so it defines the bearing life as being able to last 16.6 years. The turbine efficiency result is 0.94, calculated using the data specifications in the Taluda'a PLTM or (MANUAL BOOK). Then, the results obtained by KW every day depend on the air flow entering the turbine. Calculated using specifications, it can produce 991.2 Kw per 1 unit. Meanwhile, the Taluda'a PLTM uses two teams, so the Kwh made is 991.2 Kw x2, calculated using the Taluda'a PLTM specification data. Evaluation of the average net capacity from 2022 to 2023 experiences an increase and decrease in Kwh produced due to the rainy and dry seasons.